Synthesis, structure, and properties of switchable cross-conjugated 1,4-diaryl-1,3-butadiynes based on 1,8-bis(dimethylamino)naphthalene - Tsybulin, Semyon V.; Filatova, Ekaterina A.; Pozharskii, Alexander F.; Ozeryanskii, Valery A.; Gulevskaya, Anna V. (Beilstein Journal of Organic Chemistry, 2023)
A set of novel 1,4-diaryl-1,3-butadiynes terminated by two 7-(arylethynyl)-1,8-bis(dimethylamino)naphthalene fragments was prepared via the Glaser–Hay oxidative dimerization of 2-ethynyl-7-(arylethynyl)-1,8-bis(dimethylamino)naphthalenes. The oligomers synthesized in this way are cross-conjugated systems, in which two conjugation pathways are possible: π-conjugation of 1,8-bis(dimethylamino)naphthalene (DMAN) fragments through a butadiyne linker and a donor–acceptor aryl–C≡C–DMAN conjugation path. The conjugation path can be “switched” simply by protonation of DMAN fragments. X-ray diffraction, UV–vis spectroscopy and cyclic voltammetry are applied to analyze the extent of π-conjugation and the efficiency of particular donor–acceptor conjugation path in these new compounds. X-ray structures and absorption spectra of doubly protonated tetrafluoroborate salts of the oligomers are also discussed.
Keywords: 1,8-bis(dimethylamino)naphthalene; cross-conjugated systems; 1,4-diaryl-1,3-butadiynes; donor–acceptor systems; Glaser–Hay reaction